PENGARUH HARGA, PROMOSI DAN KEBERAGAMAN PRODUK TERHADAP MINAT BELI PADA TOKO SAMI MAKMUR - Wibowo, Andrik; Samari, Samari; Ratnanto, Sigit (Universitas Nusantara PGRI Kediri, 2022)
This study aims to examine and analyze effect of price, promotion and product diversity on buying interest at the prosperous sami shop in the village of Gondang Bojonegoro. This study uses quantitative causality approach. Data were obtained from questionnaires distributed to consumers who had bought or who were about to buy at the Sami Prosperous shop in the village of Gondang Bojonegoro. The population this study unlimited. Results of next study were tested with multiple linear regression and to test this, first the data met the requirements of the classical assumption test, also to find out the contribution of price, promotion and product diversity to buying interest was tested with a coefficient determination. The results of the two tests, namely price, promotion and product diversity have a significant effect partially and simultaneously on buying interest.